Práticas pedagógicas para a educação das relações étnico-raciais numa escola quilombola da rede municipal de João Pessoa, PB - Moura, Ronnie Wesley Sinésio (2023)
Brazilian education was historically characterized by a racist and exclusionary perspective, so that it has contributed to the discriminatory formation of the racial and ethnic composition of students, especially in Youth and Adult Education (YAE), segregating their cultural representations, in particular for black and brown people. With regard to that, this thesis’ study object is the pedagogical practices of YAE teachers, who carry out their activities in a quilombola school, and their contributions to an education concerned with race and ethnic issues. As the main problem, we have the following question: in what way do the pedagogical practices of YAE teachers at a quilombola school in the municipal education network of João Pessoa, in the Brazilian state of Paraíba, contribute to to an education concerned with race and ethnic issues and, consequently, to an anti-racist education? In order to answer this question, our general objective is to analyze how the pedagogical practices of YAE teachers contribute to to an education concerned with race and ethnic issues, in a quilombola school in the municipal education network of João Pessoa. As specific objectives, the study aimed to get to know the pedagogical practices developed by YAE teachers in a quilombola school; to identify whether the discourses embodied in the pedagogical practices of these teachers contribute to to an education concerned with race and ethnic issues; to investigate whether the discourses present in school documents referring to YAE are based on an anti-racist perspective; and to recognize the conceptions of these teachers on the subject of race and ethnic issues and their relationship with their pedagogical practice, developed in a quilombola school. The research’s epistemological foundation is aligned with the decolonial and Afrocentric perspectives. The research is characterized as qualitative, within the school practice ethnography approach, based on André (2012). Five YAE teachers from a quilombola school from the municipal education network of João Pessoa took part in the research. To generate the data, we carried out participant observation, field diary, document analysis and semi-structured interviews. We used Fairclough’s Critical Discourse Analysis (CDA) to analyze the data. The results indicate that the YAE teachers interviewed do a job that seeks to intersect race and ethnic issues with the content of their curricular components, with more confidence and in a more grounded way, but recognizing that there are personal and professional limits that need to be overcome. Therefore, we conclude that the research participants, when working on race, ethnic and quilombola issues in the classroom contribute to strengthening the race and ethnic belonging of the students, reinforcing the thesis that these YAE teachers from a quilombola school, even with all the setbacks and contradictions, when relating the contents of their curricular components to race, ethnic and quilombola issues, contribute to an education concerned with race and ethnic issues for the students, presenting an anti-racist discourse and epistemic-methodological stance, materialized in their pedagogical practices, resulting from the professional and personal (political, ethical and social) commitment built up by their experiences in the quilombola school space and in their participation in teacher training courses held on the school premises, putting a strain on the Eurocentric school curriculum and didactic-pedagogical attitudes that are still sedimented in the school.